Using a social media project as a way to get students to communicate conservation messages to the general public - Shrader, Adrian M.; Louw, Ina (Journal of Biological Education, 2021)
For conservation biologists to be effective, they need to be able to communicate to the general public. In today’s world, communicating means tapping into social media platforms. To get our final-year undergraduate students to engage with using social media as a communication tool, we had each of them create a video, blog, or podcast about a conservation issue they were passionate about. We provided guidance throughout the process but used self-regulated learning as our framework to get the students to engage with the learning process. We further expanded on this by having the students peer-mark 20 of their classmates’ projects. This achieved three outcomes, 1) they critically assessed content, 2) it exposed them to topics not covered in class, and 3) they could compare their achievements with those of their peers. To measure our success, we conducted an anonymous survey at the end of the course. Student feedback was very positive with creative freedom, peer-marking, and exposure to science communication being frequent responses. Ultimately, the project achieved our educational goals of fostering self-regulated learning and exposing the students to 21st century skills (e.g. critical thinking, creativity, communication, ICT skills) that they would likely use in their future careers.
Publisher: Routledge _eprint: https://doi.org/10.1080/00219266.2021.1924231
Keywords: Blog; YouTube; peer assessment; podcast; science communication; self-regulated learning